Outcome of Four Layered Bandaging in Venous Leg Ulcer due to Varicose Veins - Karmacharya, Robin Man; Vaidya, Satish; Yadav, Binay; Kunwar, Kajol; Pote, Sneha; Manandhar, Anu; Bhandari, Niroj; Bhatt, Swechha (Annapurna Journal of Health Sciences, 2026)
Introduction: Venous ulcer is the late sequele of venous diseases like varicose veins, deep vein thrombosis. Four layered bandaging (4LB) is a multicomponent elastic bandaging technique used for the treatment of venous ulcer. However, the efficacy of this treatment in our context hasn’t been well studied. The main aim of this study was to know the outcome of 4LB bandaging in venous ulcer due to varicose veins in patients presenting to university hospital of Nepal. Methods: This cross-sectional study included patients with venous ulcers secondary to varicose veins presenting to the Vascular Unit outpatient department at Dhulikhel Hospital from January 1, 2021, to October 31, 2022. All eligible patients were treated with four-layer bandaging (4LB). Patients with concomitant arterial disease (ankle–brachial index <0.8 with symptoms such as claudication, ischemic ulcer, or gangrene) were excluded. Ulcer area and stage were recorded before 4LB application and reassessed at 7 days and 30-day follow-up. Data were analyzed using IBM SPSS Statistics version 13.0. Continuous variables were compared using the independent sample t-test and categorical variables using the Chi-square test. A p value <0.05 was considered statistically significant. Results: Four layer bandaging for venous ulcer was done in a total of 46 participants. Among them, 31 were male and 15 were female. The mean age of the participants was 46.8 years. 36 participants had the first occurrence of ulcer while the rest of them had recurrence. The duration of ulcer time was seven months with the mean area of ulcer 2.5cm2. Following 4LB bandaging, the mean area decreased to 1.9cm2 in 1 week and 1.2cm2 in 1 month. 24 (54.4%) of them had healing of venous ulcers from Stage C6 to Stage C5 according to CEAP classification. Conclusions: Newer bandaging techniques like 4LB is a recommended treatment modality for venous ulcer due to varicose veins. Once optimized these cases should undergo further treatment such as RFA and other adjunct procedures where applicable.